Features of estimation of left ventricular geometry in patients with arterial hypertension - V. V. Syvolap; Ye. V. Novikov; V. A. Lysenko; A. O. Bogun (Zaporozhye State Medical University, 2017)
Aim: To compare the influence of the methods of calculating MMLV for Penn Convention and ASE on the distribution of left ventricular geometry types in patients with hypertension, to find out additional echographic criteria that will help to offset differences in the estimation of types of geometry. Materials and methods: The study involved 100 patients with essential hypertension ІІ degree, ІІ stage, aged from 18 to 79 years (mean age 54.71 ± 13.93 years, 44% men). Echocardiography was performed on Esaote My Lab Seven (Italy) according to generally accepted rules. The distribution according to the types of left ventricular geometry was carried out in accordance with the recommendations for quantifying the structure and function of the left ventricle. Under normal index of MMLV, the main types of geometry were: normal geometry and concentric remodeling; in elevated - concentric and eccentric LVH. Additionally, all the patients underwent dopplerography of transvalvular flows in pulsed-wave and continuous-wave modes, and the velocity of the fibrous rings of mitral and tricuspid valves were determined. Statistical processing of the material was carried out using the software package "Statistica 6.0" (StatSoft, Tulsa, OK., S.S.A.) and "Analyse-it for Microsoft Excel 4.80.1" (Analyse-it Software, Ltd.). The t-criterion of the Student, Mann-Whitney, Kruskal-Wallis, χ2 was used. The ROC-analysis was used to determine the cut-off value of quantitative indicators. The significance of differences was considered at the level of p<0.05. Results. Using the ASE formula, the normal left ventricular geometry was determined significantly more often (43% vs. 26%, p = 0.0122) than when calculated by the Penn Convention formula. Concentric remodeling also probably prevailed when calculated by ASE (13% vs. 5%, p = 0.0495). When calculating using the Penn Convention method, the number of cases of eccentric hypertrophy was significantly higher (44% vs. 27%, p = 0.0128) than with the application of the ASE formula. The use of the additional echographic criterion - the speed of the early movement of the medial fibrous ring MK <8 cm / s allows the same percentage distribution of patients with GC according to the types of LV geometry, regardless of the used formula for calculating MMLF (ASE or Penn Convention). Conclusion. The formula for the calculation of the Penn Convention of the index of MMLV overestimates the degree of pathological changes in the myocardium in patients with arterial hypertension, mainly due to an increase in the specific gravity of cases of eccentric hypertrophy, while the formula for calculating the index of MMLV for ASE increases the number of patients with EH with normal LV geometry. The inverse correlation between the mass of the myocardial infarction and the speed of early motion of the medial fibrous ring of MK was found (r = -0,29; p = 0,004). Consideration of an additional criterion for the speed of the early movement of the medial fibrous ring Ea medial <8 cm / s completely alleviates the error in the distribution of types of geometry that arises when using only two criteria - the RST and the index of MMLV calculated by any formula (ASE or Penn Convention).